Pengaruh Kepuasan Kerja Dan Keterlibatan Karyawan Terhadap Kinerja Karyawan PT Thamrin Brother Sudirman - Mohammad Kurniawan Darma Putra (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to determine whether there is influence between job satisfaction and employee involvement on employee performance at PT. Thamrin Brothers Sudirman Palembang branch. The number of samples in this study amounted to 20 employees. The data collection technique in this study was by means of a questionnaire. Data analysis using multiple linear regression analysis model. From the results of research conducted simultaneously on the variables of job satisfaction and employee involvement in the acquisition of F count (2.819) > table F value (2.12) and F significance value (0.008) < error rate (α = 0.05), then H3 Accepted, so it can be interpreted that job satisfaction, employee involvement have a significant effect on employee performance. A constant of 24,775 states that if the independent variables (Job Satisfaction and Employee withdrawal) are considered constant, then the employee's performance is 24,775. The regression coefficient of the job satisfaction variable affects employee performance by -0.184 or has a negative effect, which means that if the job satisfaction variable increases by 1%, then on the contrary the performance variable will decrease by 0.184. Assuming that other variables remain constant. The regression coefficient of the employee involvement variable affects employee performance by 0.656 or has a positive effect, which means that if the work involvement variable increases, it affects employee performance and will increase by 0.656.